Agronomic biofortification of cowpea with zinc: Variation in primary metabolism responses and grain nutritional quality among 29 diverse genotypes - Silva, Vinícius Martins [UNESP]; Nardeli, Ana Júlia [UNESP]; Mendes, Nandhara Angélica de Carvalho [UNESP]; Rocha, Maurisrael de Moura; Wilson, Lolita; Young, Scott D.; Broadley, Martin R.; White, Philip J.; Reis, André Rodrigues dos [UNESP] (Elsevier, 2021)
Dietary zinc (Zn) deficiency is widespread globally, and is particularly prevalent in low- and middle-income countries (LMICs). Cowpea (Vigna unguiculata (L.) Walp) is consumed widely in LMICs due to its high protein content, and has potential for use in agronomic biofortification strategies using Zn. This study aimed to evaluate the effect of Zn biofortification on grain nutritional quality of 29 cowpea genotypes. Zn application did not increase cowpea yield. In 11 genotypes sucrose concentration, in 12 genotypes total sugar concentration, and in 27 genotypes storage protein concentration increased in response to Zn supply. Fifteen genotypes had lower concentrations of amino acids under Zn application, which are likely to have been converted into storage proteins, mostly comprised of albumin. Phytic acid (PA) concentration and PA/Zn molar ratio were decreased under Zn application. Six genotypes increased shoot ureides concentration in response to Zn fertilization, indicating potential improvements to biological nitrogen fixation. This study provides valuable information on the potential for Zn application to increase cowpea grain nutritional quality by increasing Zn and soluble storage protein and decreasing PA concentration. These results might be useful for future breeding programs aiming to increase cowpea grain Zn concentrations through biofortification.
Keywords: Amino acids; Phytate; Phytic acid; Protein; Sugars; Ureides; Vigna unguiculata (L.) Walp